Institutional determinants of successful public–private partnerships in electricity generation: Evidence from Tanzania - KARANKAGO, Evos M. (Journal of Sustainable Energy and Environmental Development, 2025)
Public – Private Partnerships (PPPs) have become a popular global strategy for addressing energy infrastructure challenges. However, the question on which PPPs model works best for a particular project in the range of more than a dozen different models, remains unsettled by different governments of the world. This study examined the necessary conditions for enhancing Public- Private Partnership (PPPs) models for improving electricity generation in Tanzania. Overall, the study findings revealed that, performance of PPPs in electricity generation projects was being hindered by elements such as unpredictable payments guarantee, skewed contracts for PPAs, lack of transparency and fair competition and high costs of electricity. Findings suggests that, the quality of political, economic and social institutions, both formal and informal are important for influencing the functioning of PPPs projects and its economic outcomes. Also, robust and inclusive institutions, the quality of governance structures, laws, rules, regulations, and policies as well as the accepted norms and customs, predict the best outcomes. The reverse is equally true. In addition, rent seeking activities decrease appreciably as institutional competence improves accordingly as well as the capacity of the state to regulate activities of private investors. Keywords. Public – Private –Partnerships, Independent Power Producers, Electricity generation projects, Tanzania. JEL. L32, Q48, O43. SDG. SDG7, SDG16.